2013
DOI: 10.1039/c3dt32472a
|View full text |Cite
|
Sign up to set email alerts
|

Novel vanadium(iii) complexes with rigid phenylpolycarboxylate ligands: synthesis, structures and application in C–H bond activation

Abstract: Two novel vanadium(III) complexes: V(dipic)(Hbdc)(H2O)2 (1) and [V2(dipic)2(H2btec)(H2O)4]·2H2O (2) (H2dipic = 2,6-pyridinedicarboxylic acid, H2bdc = 1,3-benzene-dicarboxylic acid, H4btec = 1,2,4,5-benzenetetracarboxylic acid) are synthesized by the reaction of V2(SO4)3, 2,6-pyridinedicarboxylic acid and 1,3-benzene-dicarboxylic acid (for 1) or 1,2,4,5-benzenetetracarboxylic acid (for 2) under hydrothermal condition at 120 °C for 3 days. They were characterized by elemental analysis, IR, UV-Vis, single crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…We found that a copper complex could be used in catalyzing oxidative bromination, the catalytic activity of which is similar to that of the bromoperoxidase [30]. For exploring new stable biomimetic catalysts and effect of different kinds of ligands on the catalytic activity, we have chosen two arene-linked pyrazolyl methanes as ligands, 1,4-bis((1H-pyrazol-1-yl)methyl)benzene (L1) and 1,4-bis((3,5-dimethyl-1H-pyrazol-1-yl)methyl)benzene (L2), to synthesize two new copper complexes, [Cu 2 …”
Section: Introductionmentioning
confidence: 92%
“…We found that a copper complex could be used in catalyzing oxidative bromination, the catalytic activity of which is similar to that of the bromoperoxidase [30]. For exploring new stable biomimetic catalysts and effect of different kinds of ligands on the catalytic activity, we have chosen two arene-linked pyrazolyl methanes as ligands, 1,4-bis((1H-pyrazol-1-yl)methyl)benzene (L1) and 1,4-bis((3,5-dimethyl-1H-pyrazol-1-yl)methyl)benzene (L2), to synthesize two new copper complexes, [Cu 2 …”
Section: Introductionmentioning
confidence: 92%
“…Hence Cy cannot be effectively oxidized by H 2 O 2 without the participation of an acid additive, with conversions of only 6-8 % (entries 1 and 2). Upon the addition of HNO 3 to the system, similar complexes often show high catalytic activities [28][29][30]. However, complexes 1 and 2 were still inert for Cy oxidation with HNO 3 as additive (entry 3), although the conversion was reached to 75/88 %.…”
Section: Catalysis Studymentioning
confidence: 97%
“…To our best knowledge, the Cy oxidation promoted by some iron-chromium, vanadium and copper complexes is more efficiently in acidic media [34][35][36][37] , such as HNO 3 [6,8,9] , CH 3 COOH [34] , CCl 3 COOH [34] , HCl [34] , H 2 SO 4 [34] , oxalic acid [14,38] , pyrazine-2,3-dicarboxylic acid [38] and pyrazine-2-carboxylic acid [39] .…”
Section: Effects Of Different Acidsmentioning
confidence: 99%
“…Pokutsa et al [14] advised that oxalic acid and glyoxal can noticeably increase the catalytic activity of VO(acac) 2 in Cy oxidation. However, the investigation on the effective additives for the VO(acac) 2 [9] . Herein, we found that the VO(acac) 2 -catalyzed process can be strongly improved by o(m,p)-phthalic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation